EVALUASI IMPLEMENTASI SISTEM INFORMASI MANAJEMEN AKUNTANSI BARANG MILIK NEGARA (SIMAK-BMN) TERHADAP PENGELOLAAN ASET NEGARA - Sari, Ayu Desita (Universitas Muhammadiyah Jember, 2018)
This study was conducted to find out how the mechanism of recording, administration and reporting of state property through the SIMAK-BMN application designed by the financial accounting system application team under the treasury system directorate of the finance department in an effort to realize BMN Report transparency and accountability. The method used in this study is descriptive qualitative approach to literature study through government regulations, scientific books, scientific journals and articles on the internet. From the overall analysis of the literature carried out it can be concluded that with the SIMAK-BMN Application the recording of fixed assets is more patterned or systematic, and makes it easier to produce BMN reports. Keywords: Recording, Administration, Reporting, SIMAK-BMN, Transparency, and Accountability